Event-Based Optimization of Tourism at Pasir Padi Beach, Pangkalpinang City - Fauzi, Dani; Yulfi , Muhamad Raehan Nur Alim; Indriani, Indriani (International Journal of Magistravitae Management, 2024)
Pasir Padi Beach, located in Pangkalpinang City, Bangka Belitung Island Province, has become a major tourist destination by hosting various events that attract local and foreign tourists. This study aims to optimize event-based beach tourism at Pasir Padi Beach by analyzing social, economic, infrastructural, and cultural impacts. Data were gathered through interviews with the Pangkalpinang City Tourism Office, observations, and secondary sources. The findings indicate high community participation, enhanced social cohesion, and significant economic benefits for local MSMEs, with income increases of 60-80% during events. However, challenges such as inadequate community readiness, lack of market research, and suboptimal stakeholder synergy were identified. To address these challenges, a comprehensive strategy is proposed, including improving infrastructure, diversifying events, and integrating local cultural elements to balance tourism development and cultural preservation. Government support, combined with local community empowerment and strong stakeholder collaboration, is essential. Effective marketing strategies, utilizing social media and influencers, and the implementation of sustainable tourism practices are recommended to maximize economic benefits while preserving environmental and cultural integrity. In conclusion, with strategic improvements in infrastructure, event management, and stakeholder involvement, Pasir Padi Beach can become a model for sustainable event-based beach tourism, promoting economic growth, social cohesion, and cultural preservation. The study’s limitation is the reliance on a single informant from the Tourism Office, which may limit perspective diversity. Future research should involve a wider range of stakeholders, including MSMEs, youth groups, local artists, and private sector representatives, to provide a more comprehensive understanding.